2007
DOI: 10.1203/pdr.0b013e318156887a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ala12 Allele in the PPARγ-2 Gene on the Relationship Between Birth Weight and Body Composition in Adolescents: The AVENA Study

Abstract: ABSTRACT:The intent of this study was to assess whether the effect of birth weight on later body composition is modified by Pro12Pro, Pro12Ala, and Ala12Ala genotypes of the peroxisome proliferator-activated receptor ␥-2 (PPAR␥-2) gene. The PPAR␥-2 gene polymorphism was genotyped in 273 adolescents aged 13-18.5 y, born at term and whose birth weight was known. They were selected from a cross-sectional multicenter study conducted in five Spanish cities in 2000 -2002. Body mass index (BMI) was calculated from we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…The follow-up of our study group will show whether the finding applies to Finnish children with PA. The results regarding the relationship between the minor Ala12 variant and birth measures have been contradictory [20,27,29,30]. The biggest studies on infants have shown no difference in birth measures concerning Pro12Ala polymorphism of PPARG [30], which is in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…The follow-up of our study group will show whether the finding applies to Finnish children with PA. The results regarding the relationship between the minor Ala12 variant and birth measures have been contradictory [20,27,29,30]. The biggest studies on infants have shown no difference in birth measures concerning Pro12Ala polymorphism of PPARG [30], which is in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Adolescents carrying the Ala12 allele in the PPARg-2 gene lower birth weight was associated with lower lean body mass, whereas the associations in the Pro12Pro group disappeared after adjustment for potential confounders. 54 In summary, our findings suggest that subcutaneous fat mass in early childhood is at least partly established in fetal life and may have consequences for adiposity in later life. Follow-up studies are needed to assess whether subcutaneous fat mass in early childhood tracks to adulthood, and whether and to what extent the effects of parental, fetal anthropometrics and postnatal growth patterns on subcutaneous fat mass persist.…”
Section: Discussionmentioning
confidence: 59%
“…[26] The genetic determinism is decisive in influencing birth weight (ponderal index [PI]) corresponding to the length and adult metabolic disorders, and vice versa. [27,28] …”
Section: Introductionmentioning
confidence: 99%